Educational Production in East Asia: The Impact of Family Background and Schooling Policies on Student Performance - Ludger Wößmann (Kiel Institute for World Economics (IfW), 2003)
East Asian students regularly take top positions in international league tables of educational performance. Using internationally comparable student-level data, I estimate how family background and schooling policies affect student performance in five high-performing East Asian economies. Family background is a strong predictor of student performance in South Korea and Singapore, while Hong Kong and Thailand achieve more equalized outcomes. There is no evidence that smaller classes improve student performance in East Asia. But other schooling policies such as school autonomy over salaries and regular homework assignments are related to higher student performance in several of the considered countries.
Keywords: I20; H52; O15; 330; Education production function; East Asia; family background; class size; school autonomy; Bildungsniveau; Allgemeinbildende Schule; Familiensoziologie; Schulpolitik; Schätzung; Ostasien; Hongkong; Japan; Südkorea; Singapur; Thailand; TIMSS